1972
DOI: 10.1083/jcb.53.3.737
|View full text |Cite
|
Sign up to set email alerts
|

Structural Alteration in Isolated Rat Liver Nuclei After Removal of Template Restriction by Polyanions

Abstract: Specific polyanions release DNA template restrictions for DNA synthesis in isolated rat liver nuclei. The degree to which DNA synthesis is enhanced can be correlated with a spectrum of changes in nuclear structure Each polyanion which is effective in the release of template restriction produces a characteristic alteration in nuclear ultrastructure. Polyanions which have no effect on DNA synthesis do not appear to cause any change in nuclear organization or ultrastructure. Parallel measurements of nuclear DNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1973
1973
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Several biochemical studies have indicated the involvement of glycosaminoglycans in nuclear functions (Stein et al, 1975;Bhavanandan and Davidson, 1975; for a review, see Lindahl and Hook, 1987). In particular, heparin has been shown to induce dispersion of chromatin structure (Arnold et al, 1972;Cook and Aikawa, 1973;Smith and Cook, 1977) and to stimulate the DNA template characteristic of chromatin and nuclei during DNA synthesis (Kraemer and Coffey, 1970). Although hyaluronic acid has been identified as the major component of nuclear glycosaminoglycans in isolated rat liver nuclei (Furukawa and Terayama, 1977), to date its function in the nucleus is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several biochemical studies have indicated the involvement of glycosaminoglycans in nuclear functions (Stein et al, 1975;Bhavanandan and Davidson, 1975; for a review, see Lindahl and Hook, 1987). In particular, heparin has been shown to induce dispersion of chromatin structure (Arnold et al, 1972;Cook and Aikawa, 1973;Smith and Cook, 1977) and to stimulate the DNA template characteristic of chromatin and nuclei during DNA synthesis (Kraemer and Coffey, 1970). Although hyaluronic acid has been identified as the major component of nuclear glycosaminoglycans in isolated rat liver nuclei (Furukawa and Terayama, 1977), to date its function in the nucleus is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A numimplies a fundamentally new paradigm for the regulation ber of polyanions, such as dextran sulfate and heparin, of gene action. According to current models of gene have powerful immunological properties, some of which expression, transcription is controlled by regulatory proare shared with bacterial DNA (Arnold et al, 1972; Vogt teins that bind to specific promoter regions and affect et al, 1973;Smith et al, 1990). The CpG motifs may transcription rates.…”
Section: Tivity Ure 1) Because Of the Presence Of Extended Dg Runs Inmentioning
confidence: 99%
“…For this purpose, DNA histograms were recorded in the presence of heparin, a polyanionic glycosaminoglycan, which is known to probe the chromatin structure. Heparin specifically interacts with the histones within the repressed heterochromatin [12][13][14][15][16][17][18]. DNA in condensed chromatin provides fewer binding sites for dyes than DNA in dispersed chromatin does [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%